2016
DOI: 10.1111/jphp.12592
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid inhibits cholestatic liver injury induced by α-naphthylisothiocyanate: involvement of STAT3 and NFκB signalling regulation

Abstract: These data suggest that CGA inhibits both ANIT-induced intrahepatic cholestasis and the liver injury. This protective effect involves down-regulation of STAT3 and NFκB signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…IL-10 inhibits the binding of NF-κB with DNA activity from the cytoplasm to the nucleus by inhibiting the activity of nuclear factor (IKK), inhibits the NF-κB activity, and reduces the release of TNFα, thereby reducing the inflammatory response (7). Thus, the data suggest that quercetin significantly suppressed NF-κB in ALD mice.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…IL-10 inhibits the binding of NF-κB with DNA activity from the cytoplasm to the nucleus by inhibiting the activity of nuclear factor (IKK), inhibits the NF-κB activity, and reduces the release of TNFα, thereby reducing the inflammatory response (7). Thus, the data suggest that quercetin significantly suppressed NF-κB in ALD mice.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the metabolism of alcohol in the liver results in a large number of free radicals, which inhibits fatty acid oxidation, accumulates intrahepatic fat when beyond the body's clearing ability, and also leads to lipid peroxidation of liver cell membrane, resulting in liver cell damage (12). At the same time, these reactive oxygen species will increase the level of endotoxin, and lead to the release of inflammatory mediators, which can also make NF-κB activated, thus generating a large number of inflammatory mediators, to have an inflammatory cascade amplification effect, aggravating liver damage (7). Quercetin ( Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanisms of STAT3 inhibition by ACE and active ingredients inhibiting STAT3 activity remain elusive. Several compounds in ACE including capillarisin, scoparone, scopoletin and cholorogenic acid have been reported to suppress the activity of STAT3 (24,(29)(30)(31). Thus, it can be postulated that several compounds in ACE are responsible for STAT3 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs Celastrol (27) Andrographolide (28) Rosuvastatin (29) Shenqi Fuzheng Injection (30) Peroxiredoxin 4 (31) 9-cis-retinoic acid (32) Schisandrol B (33) Glechoma hederacea (34) Chicken bile powder (35) Auraptene (36) SRT1720 (37) Sweroside (38) Chlorogenic acid (39) Vitamin C (40) Thymoquinone (41) Cilostazol (42) Quercetin (43) Guava Pulp (44) Serotonin (45) Docosahexaenoic acid (46) Cyclopamine (47) Resveratrol (48) Caffeic acid phenethyl ester (49) Tetrathiomolybdate (50) Aminoguanidine ( IL-1alpha, TNF-alpha a novel membrane-bound bile acid receptor expressed in many types of cells, which plays an important role in regulating energy homeostasis and glucose metabolism. In vitro experiments showed that TGR5 significantly inhibited macrophage function (66).…”
Section: Drug Therapy For Cholestatic Liver Injurymentioning
confidence: 99%